청년 창업농의 성공적 정착에 미치는 요인 분석 - 마상진; 김남훈 (농촌경제, 2019)
As aging is the biggest problem in the rural community of South Korea, fostering young farmers is the most effective policy to solve the aging problem. Thus, in this study, we investigate significant factors that affect young beginning farmers’ successful settlement in rural communities. We used the young beginning farmers’ settlement survey which was conducted by the Korea Rural Economic Institute in 2017. We analyzed young beginning farmers’ income and their quality of life for their successful settlement by employing left-censored tobit and ordered logistic regression. The estimation results show that succession of a farm from parents, sufficient start-up funds, and keeping the books are the significant factors to increase young beginning farmers’ income. The results also show that low conflicts with local residents, a good relationship with the community, and enough agricultural income for a living are the significant factors to improve their quality of life.